So, since y= -7x + 15, and it also equals 5x - 9, you can take what y equals (either one works in this scenario) so lets take the 5x - 9. since this is what y equals, you can take that expression and replace y with it in the other equation. After you do this you'd get 5x - 9 = -7x + 15. Now both sides of this equation are equal to y. To find the solution, you solve for the variable. After you do this, you get x = 2. Now that you know what x is, you can plug that into any of the original equations to find y. lets use y = 5x - 9 again. This time, substitute x with the number you found earlier, 2. Then you solve. It should look like this: y = 5(2) - 9. So y is 1. There is your answer, x = 2, y = 1.